Investigation of the Effects of Wafer-Baking Plates on Thermal Distribution, Wafer Thickness, and Wafer Color Distribution - Uğur Köklü; Abdullah Sadık Tazegül; Fatih Serin; Gültekin Basmacı (Applied Sciences)
Wafer-baking ovens are machines that bake liquid batter by heating the interconnected cast plates in a gas oven. The plates in contact with the wafer batter are generally made of the cast material. Although there are many studies on the contents in the recipes of wafer products and the effects of the additives included in the recipes on the quality of the wafer sheet, there are few studies on the effects of the material type of the wafer-baking plate on the baking process. In this study, the thermal distribution of two baking plates made of different materials (GG-25 gray cast iron and GJV-350 vermicular cast iron), their effects on the thickness of the wafer sheet, and their effects on the color distribution of the wafer sheet were investigated at different baking rates. The experiments were conducted in an industrial wafer-baking oven at two different production rates. As a result, it was observed that the GJV-350 vermicular casting plate provides a more homogeneous heat distribution, more stable wafer sheet thickness, and more homogeneous color distribution of the wafer sheet at a maximum production rate.